(untitled) (Communication & Society, 2017)
The fast-changing digital media environment has provoked new communication processes in contemporary society. In particular, younger generations engage in new ways of interacting with each other thanks to the constant emergence of digital technologies and mobile communication outlets. New habits arise every year, changing not only our interpersonal communication, but also our overall consumption of information and entertainment content, with video and instant messaging apps being particularly popular among younger populations. This study employs a mixed method approach to measure young Hispanics’ motivations to use smartphones in Chile, Mexico and the U.S. The subjects, 18 to 25 years old, participated in focus groups and surveys conducted in 2015: 55 Hispanic smartphone users joined focus groups whilst 1,403 respondents completed surveys in Chile, Mexico and Texas (U.S.). Results show similarities and differences in young Hispanics’ motivations and uses of smartphones, including the personal and commercial value they ascribe to information, time spent on social networks, and their preferences for mobile devices compared to other media. The findings are used to develop three archetypes of young users, based on smartphone’s motivations and uses. Utilizing factor analysis scores, a linear regression analysis was conducted to identify the main traits of these three archetypes: “always connected,” “entertained,” and “secure.”